Influence of drying and storage conditions on viability of neem seeds (Azadirachta indica A. juá) - Fornos Reyes, Digno Marvin (Uppsala (Sweden), 1997)
Sumario (En)
Ilus.; 33 ref.
Tesis (Mag Sc)
Keywords: AZADIRACHTA INDICA; ALMACENAMIENTO DE SEMILLAS; VIABILIDAD DE LA SEMILLA; SEMILLAS; NICARAGUA